THE IMPORTANCE OF SERIAL VERB CONSTRUCTIONS - Mannobova Lola Abdunazar qizi , (Journal of new century innovations, 2023)
Abstract: Serial verb construction is known as a serialization of verbs in which two or more verbs or verb phrases are connected with each other within a single clause. The verbs in the series must share some grammatical properties such as tense, aspect and polarity. This article gives an overview about the importance of SVCs identifying some examples in many different spoken languages from all around the world.